Perancangan Interior Museum MotoGP Legends di Surabaya - Kevin Christopher; Sriti Mayang Sari; Dodi Wondo (Intra, 2017)
MotoGP is a sport that uses motor vehicles with high speed to race to be able to get past the finish line first. This design aims to provide facilities for the community, especially the lovers of motogp in Surabaya, This design concept is futuristic design to support the objects on display so it does not look out of date. This design also provides facilities to increase community insight such as information about MotoGP legends, there is also a hall to carry out various activities related to motorsport, there is also a retail store that sells various MotoGP tributes and cafes so that visitors can relax for a moment After touring at this legends MotoGP museum.